Actualización de la distribución de triatominos en Colombia y nuevos registros de infección con Trypanosoma cruzi en La Mesa, Cundinamarca (2020)
Chagas disease is a zoonotic disease caused by the infection of Trypanosoma cruzi. This parasite is characterized by a genetic diversity that groups it in 6 DTUs (Discrete Typing Units) and for having complex transmission cycles involving a wide range of hosts. The vectors of T. cruzi are insects of the subfamily Triatominae, an ecologically diverse group including 151 species. In Colombia, Chagas disease is considered endemic in up to 40% of its territory and there are 27 triatomine species reported. The distribution of these species has been previously reviewed in the country by Guhl et al. in 2007 but hasn?t been updated since. In this paper we used occurrence data between 2007 and 2020 from different sources, including insects collected between 2018 and 2019, to establish an updated geographical and altitudinal distribution for the triatomine species in Colombia. Parasite identification and genotypification was performed in the collected triatomines between 2018 and 2019, identifying TcI DOM in Rhodnius prolixus and TcI sylvatic in Rhodnius pallescens from La Mesa, Cundinamarca, and TcI sylvatic in Triatoma maculata from Santa Marta, Magdalena. Regarding the distribution of triatomines in Colombia, 508 municipalities were added to the different species known in the country and using Geographic Information Systems (GIS) the general richness patterns of the subfamily were described. With this update Panstrongylus geniculatus is the most widely distributed triatomine in Colombia while the species with the greatest altitudinal ranges remain Rhodnius prolixus and Triatoma dimidiata.